Humor Style and Academic Success in a Blended Learning Setting among Technical University Students - Sarala Thulasi Palpanadan; Khairunesa Isa; Nurliyana Md Rosni; Wan Hanim Nadrah binti Wan Muda; Binti Maunah, M.Pd.I. (Journal of Technical Education and Training, 2025)
Students’ personal growth and future employment prospects are significantly influenced by their academic performance, especially in technical education. Traditional teaching approaches have given way to blended learning as higher education increasingly incorporates information and communication technology, which can have a big impact on students’ academic achievement and psychological health. This study examines the connection between students’ academic performance and their humor preferences in a blended learning setting at a Malaysian Technical University Network (MTUN) institution. A survey using the Academic Self-Concept (ASC) and Humor Styles Questionnaire was completed by 307 students. SPSS version 26 was used to analyze the data using both descriptive and inferential statistics. According to the findings, pupils’ academic performance was mediocre, and the most popular type was self-enhancing humor. Interestingly, aggressive humor had a negative relationship with academic achievement, but affiliative and self-enhancing humor types had a favorable correlation. Self-defeating humor and academic success did not significantly correlate. According to these results, a more stimulating and encouraging learning atmosphere can be created by strategically utilizing positive humor styles, especially affiliative and self-enhancing humor. This could lower stress, boost motivation, and improve student performance. In MTUN’s technical education program, where the curriculum frequently includes difficult and complex material, comedy can be a useful teaching tool to enhance students’ academic performance and general well-being. In order to promote deeper learning, student engagement, and emotional resilience, educators ought to think about incorporating humor into their lesson plans.